2017
DOI: 10.1093/eurheartj/ehx467
|View full text |Cite
|
Sign up to set email alerts
|

A common missense variant of LILRB5 is associated with statin intolerance and myalgia

Abstract: AimsA genetic variant in LILRB5 (leukocyte immunoglobulin-like receptor subfamily-B) (rs12975366: T > C: Asp247Gly) has been reported to be associated with lower creatine phosphokinase (CK) and lactate dehydrogenase (LDH) levels. Both biomarkers are released from injured muscle tissue, making this variant a potential candidate for susceptibility to muscle-related symptoms. We examined the association of this variant with statin intolerance ascertained from electronic medical records in the GoDARTS study.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 40 publications
1
46
0
Order By: Relevance
“…Leusink et al (2014) [40] Case-control We found no association of the CYP3A4*22 minor allele (rs35599367) with the effectiveness of statins in reducing MI risk. Siddiqui et al (2017) [25] Meta-analysis Consistent association between Asp247Gly and outcomes associated with SI. Luzum et al (2015) [30] Case-control Our results do not replicate the association between GATM rs9806699 and SIM.…”
Section: Article Title Study Design Conclusionmentioning
confidence: 92%
See 2 more Smart Citations
“…Leusink et al (2014) [40] Case-control We found no association of the CYP3A4*22 minor allele (rs35599367) with the effectiveness of statins in reducing MI risk. Siddiqui et al (2017) [25] Meta-analysis Consistent association between Asp247Gly and outcomes associated with SI. Luzum et al (2015) [30] Case-control Our results do not replicate the association between GATM rs9806699 and SIM.…”
Section: Article Title Study Design Conclusionmentioning
confidence: 92%
“…One meta-analysis and one case-control showed a true association of LILRB5 mutation (rs12975366: T>C: Asp247Gly). [25] Also, possible association of HLA-DRB1 carriers with SIM through an immune-mediated necrotising mechanism by the production of an autoantibody against HMGCR, a target molecule of statin, was determined, and the association of HLA-DRB1*11:01 with antibody-positive myopathy was shown in different populations. [17] RYR2 gene…”
Section: Hla-dr and Lilrb5 Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential role for immune system genetic variation in development of statin-induced myopathy has been recently reported for a variant in leukocyte immunoglobulin-like receptor subfamily-B, LILRB5 gene (rs12975366:T > C:Asp247Gly) [25]. The missense variant Asp247Gly has been associated with serum creatine kinase (CK) levels; the mean levels of this enzyme were elevated in Asp247 homozygotes (TT).…”
Section: Lilrb5 Genementioning
confidence: 99%
“…The missense variant Asp247Gly has been associated with serum creatine kinase (CK) levels; the mean levels of this enzyme were elevated in Asp247 homozygotes (TT). The LILRB5 Asp247 homozygous genotype has, therefore, been associated with increased risk of statin intolerance [25]. No independent replication data on this plausible new variant has been available so far.…”
Section: Lilrb5 Genementioning
confidence: 99%